Cross stitch for the Earth : 20 designs to cherish - Congdon, Emma (David & Charles, 2021)
"Stitch for a greener future with designs that celebrate the majesty of Planet Earth. These 20 cross stitch patterns serve to remind us of the things we cherish in the natural world, and gently encourage us to change our habits to protect the environment." -- Back cover.